(untitled) (Research, Society and Development, 2023)
This study is justified by its academic, scientific and social relevance, based on presenting the main outcomes related to the risk of sepsis, as well as assistance and care for critically ill patients in the Intensive Care Unit. Thus, the objective of the present study focuses on: Identifying the main care for septic patients in the adult Intensive Care Unit. This study was carried out through an Integrative Literature Review carried out between February and March 2023, with the aim of investigating updates regarding sepsis. Thus, the searches took place in the scientific databases: LILACS, SCIELO and MEDLINE. Thus, selecting 11 articles to compose the final sample. With regard to professional assistance, this result indicates that the systematic search for signs of infection can lead to an early diagnosis of sepsis. Agile and adequate treatment is therefore the cornerstone of a successful approach to sepsis. Promoting the relief of pain and other discomforts is one of the main concerns in patient care. Other common symptoms such as sweating, restlessness, and dyspnoea must be recognized so that measures can be taken to promote the patient’s health. There is a need to deepen research on care provided by health professionals to patients with sepsis to ensure quality care based on scientific evidence and linked to clinical practice. The results obtained reflect the importance of managing the septic patient.